The oxidation behaviors of high-purity niobium for superconducting radio-frequency cavity application in vacuum heat treatment. (September 2022) - Yu, Mingming; Pu, Guo; Xue, Yi; Wang, Sishu; Chen, Sheng; Wang, Yihan; Yang, Li; Wang, Zhijun; Zhu, Tongtong; Tan, Teng; He, Yuan; Huang, Shichun; et al.
Abstract: To explore the impact mechanism of vacuum heat treatment on the performance of Superconducting Radio-Frequency (SRF) Cavities, especially in the medium temperature range (300–400 °C), the chemical composition on the surfaces and the impurities distribution along the depth of the high-purity niobium (Nb) samples heat-treated at 250–800 °C in Ultra High Vacuum (UHV) were investigated using X-ray photoelectron spectroscopy (XPS). The XPS results on the surface showed that the surface oxide composition varied with the different heat-treatment temperatures. Among the range of 250–600 °C, Nb2 O5 gradually reduces and suboxide such as NbO, Nb2 O, and NbOx gradually enhances with the increasing of heat-treatment temperature. However, an elevated proportion of Nb2 O5 was shown on the sample heat-treated at 800 °C. The XPS depth profiles acquired by different times of Ar + etching revealed that the oxygen concentration in depths increased after heat treatment in UHV and presented a temperature dependence, while the nitrogen was not precisely identified. This work might also contribute to understanding the effect of material properties on the RF performance and help to optimize the surface-treatment process for SRF Nb cavities. Highlights: A fundamental understanding of impact mechanism of vacuum heat treatment on high-purity niobium. The medium temperature heat-treatment niobium samples showed a low proportion of Nb2 O5 on the surface. The niobium sample heat-treated at 300 °C and 350 °C produced the higher oxygen concentration in depths. No nitrogen in depths was identified in all the heat-treatment samples.